Coluber korros Lesson, 1831 and Coluber korros Schlegel, 1837 (Reptilia: Squamata: Colubridae) : there is a korros too many in the family. - Patrick, David; Jean, Lescure; Jay M., Savage; Indraneil, Das; Olivier, S. G. Pauwels; Gernot, Vogel; Thomas, Ziegler (Magnolia Press, 2023)
The purpose of this paper is to solve an overlooked nomenclatural problem involving two taxa of Colubridae, both described as Coluber korros. The first one is Coluber korros Schlegel, 1837, now Ptyas korros, a well-known and widespread species in south-east Asia. Its senior homonym is Coluber korros Lesson, 1831, a long forgotten taxon. Furthermore, these taxa are undoubtedly non-conspecific. We tentatively identify the holotype of this latter taxon as a large specimen of Coelognathus radiatus (F. Boie, 1827) and we specify its type locality as “Region of Kolkata, West Bengal State, eastern India” (the same specification of type-locality can hence be applied to the elapid Naja kaouthia Lesson, 1831). Nevertheless, following the strict principle of priority, Coluber korros Lesson, 1831 has priority over Coluber korros Schlegel, 1837. Based on the Code, we use Article 23.9 on reversal of precedence in order to preserve the use of the well-known taxon Coluber korros Schlegel, 1837 (now Ptyas korros) against its senior primary homonym Coluber korros Lesson, 1831. Finally, we consider Coluber boncorage Lesson, 1831 to be a nomen dubium.